The Impact of Natural Disaster on Mental Health of Victims Lives: Systematic Review - Novia , Kristia; Hariyanti, Tita; Yuliatun, Laily (International Journal of Science and Society, 2020)
Natural disasters are still a matter of the world until today. The events pose not only physical impact but also psychological impacts that leave deep sorrow and fear. The survivors of the disaster felt they were at a very unsettled condition, felt very fearful, felt agitated for uncertain circumstances, and became very easily panicked until they could experience anxiety, depression, and post-traumatic stress disorder (PTSD). This systematic review aims to identify the impact–effects often posed by natural disasters on the soul health of survivors. Data searching is done on the Proquest, Pubmed, Science Direct, Sage, and Scopus databases that were converged in the 2013 to 2019 ranges. The psychological impact experienced by the victims after natural disaster events are depression, post-traumatic stress disorder (PTSD), fear, suicide experiments, and other mental health disorders such as mood changes and a loss of interest in an activity. Natural disasters can hurt the mental health of the victims. If the psychological problems that occur to the victims are not immediately addressed, the victims will fall on more mental severe disorder conditions.